Low temperature and leaf growth in grasses - Farrell, Aidan D. (Trinity College (Dublin, Ireland). Department of Botany, 2005)
The central role of temperature in regulating plant growth was investigated by analysing the temperature sensitivity of various aspects of growth in grass leaves. A study of thermal responses in the C4 grass Miscanthus found significant genotypic variation in the effect of temperature on shoot emergence, leaf extension and seedling survival. One genotype, Sin-H9, exhibited low temperature sensitivity in leaf extension rate and shoot emergence rate. Shoots of Sin-H9 also had the highest frost tolerance, which was associated with significantly lower shoot moisture content in this genotype. The reduced time to emergence and increased frost tolerance seen in Sin-H9 was incorporated into a model of Miscanthus productivity using climate data from northern Europe. The longer growing season was predicted to increase yields by up to 26 %.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin